Where we live matters: child development and informal settlements - Khumalo, Grace Tamanda Gareta (My University, 2013)
The assertion ‘where we live matters’ (Braveman, Cubbin, Egerter, and Pedregon, 2008:1) is particularly important for the attainment of the healthy and sustainable living environment that is ideal for child development. According to child developmentalists, physical and social environmental factors play a crucial role in child development. Today, the majority of children, who make up almost half of the urban population in the Third World cities, live in the informal settlements. Informal settlements have always been associated with negative child developmental outcomes. By linking the physical and social environmental factors that influence child development reviewed in the child development literature to the living environments in informal settlements, this research report reveals that there are both positive and negative child developmental outcomes emanating from informal settlements. However, the positive aspects are often disrupted due to governments’ negligence to provide essential services to informal settlements coupled with limited reference to child developmental issues in informal settlements intervention paradigms. This research calls for governments and policy makers to develop strategies that complement the positive aspects of informal settlements for the attainment of healthy and sustainable physical and social environments required for children to develop to their full potential.